STUDY OF THE POSSIBILITIES OF FINANCING THE AGRICULTURAL SECTOR IN BULGARIA - Darina STOYANOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The need for government assistance in the external economy is necessitated by other economic uncertainties, the impact of agricultural activity on the environment, and especially low and irregular cash flows in the agricultural sector. The received state and European aid in the form of various economic losses are necessary for agricultural producers. Based on the financial resources provided, the company's financial condition is stabilized and improved. This embodies a management policy in the agricultural sector in Bulgaria. The aim of the study is to look for possible options for financing agricultural producers in Bulgaria. For the purposes of the study, the analyzed period is divided into several main groups according to Bulgaria's membership in the EU and implementation of the Common Agricultural Policy: Pre-accession, First program period (2007-2013), Second program period (2014). -2020) and the Third Program Period (2021-2027). Financing in the Agricultural sector is divided into internal and external. Internal financing refers to lending by banks and support through national surcharges, through the granting of state aid. External financing is the financial means provided to farmers by the European CAP programs (ISPA, SAPARD, RDP). Based on the analysis, it is found that the liabilities of the agricultural firms are growing faster than the assets, as farmers use more loans than savings to cover their financial needs, the small producers of the sector (under 20 ha) face the most many difficulties in obtaining financing. Subsidies are mainly received from large and major firms, while small and medium-sized ones that really need these funds remain disadvantaged. The granting of subsidies is associated with economic losses and very complicated programs, the implementation of which is tied to high public costs.